Energy‐efficient user association in downlink heterogeneous cellular networks. Issue 13 (1st September 2016) - Zhou, Tianqing; Huang, Yongming; Yang, Luxi
Abstract : In this study, the authors propose an energy‐efficient user association scheme to maximise the overall energy efficiency for downlink heterogeneous cellular networks, and formulate it as a non‐linear and mixed‐integer optimisation problem. Such a problem includes user association problem and power control problem. Since the formulated problem is in a fractional and mixed‐integer form, it is challenging for designers to achieve the optimal solutions of this problem. To this end, they design an effective three‐layer iterative algorithm. In the first layer, the energy efficiency parameter is found via bisection method. In the second layer, association index and transmit power are optimised alternately. In the third layer, the user association problem is solved via dual decomposition method and the transmit power is updated by employing a power update function. In addition, they further give some convergence analyses for some parts (user association algorithm and power control algorithm) of the proposed algorithm, and also give some complexity analyses for the whole algorithm. Numerical results show that, compared with non‐energy‐efficient association, the energy‐efficient association has significant superiorities on load balancing level, system throughput and energy efficiency.